Democracy As Islamic Values: An Analysis of Rachid Ghannouchi's Thought and Its Implications for Democratic Education in Indonesia - Aris Munandar; Suwendi; Endang Susanti (AL-TAHRIR, 2026)
Research on the relationship between Islam and democracy has been extensive, but it still largely focuses on the normative compatibility between Islamic principles and democracy, with limited attention to the pedagogical implications of political Islamic thought for the strengthening of democratic education in Muslim-majority countries such as Indonesia. To address this gap, this study examines how the concept of democracy as an Islamic value in Rachid Ghannouchi's thought can be reconstructed as a normative framework for democratic education in Indonesia. This study used a qualitative approach based on literature studies with conceptual-normative analysis methods of Ghannouchi's main works, especially related to the concepts of syūrā, maqāṣid al-syarīʿah, and al-dawla al-madaniyyah, and contextualized within Indonesia’s democratic challenges. The results of the study show that Ghannouchi's thinking not only affirms the compatibility of Islam and democracy but also provides a normative-educational model that places democracy as a process of forming a citizenship ethics based on justice, benefit, deliberation, and power limitation. The findings indicate that Ghannouchi’s concepts of the civil state and the maqāṣidi approach are highly relevant in responding to Indonesia's democratic challenges, including identity polarization, structural corruption, and the shrinking of civic space although their implementation requires institutional and pedagogical adaptation. This research contributes a novel pedagogical interpretation of Ghannouchi’s thought, which has predominantly been examined within the normative Islamic political framework.